Report on the application of phytoplankton index NMASRP for reservoirs in Greece - Kemitzoglou, D.; Mavromati, E.; Tsiaoussi, V. (Ministry of Environment, Special Secretariat for Waters, 2018)
Assessment methods had been intercalibrated for lake types LM 5/7 (deep siliceous reservoirs) and LM 8 (deep calcareous reservoirs) (de Hoyos et al. 2014). In the first round of IC that Greece participated, boundaries for individual phytoplankton metrics (chlorophyll-a, total biovolume, percentage of cyanobacteria, IGA and MedPTI) were agreed (using option 1 of IC) and formally included in the 200 8 EC Intercalibration Decision. During the second round of IC, national assessment methods based on the above metrics (NMASRP for Cyprus and Portugal, MASRP for Spain and NITMET for Italy) were intercalibrated for LM 5/7 and LM 8 types. Greece had not started the operation of the monitoring network at that time, and thus had not submitted its national assessment method for the second round of IC. The operation of the Greek monitoring network started in 2012, following the publication of a Joint Ministerial Decision in 2011. Fifty lake water bodies have been included in the monitoring network, out of which 15 are LM 5/7 and 5 are LM 8 reservoirs. The national phytoplankton assessment method applied for Greek LM 5/7 and LM 8 reservoirs is the New Mediterranean Assessment System for Reservoirs Phytoplankton (NMASRP), that has been intercalibrated in the Med GIG, as applied by Cyprus and Portugal (i.e. the metric percentage of cyanobacteria is replaced by the metric biovolume of cyanobacteria, in order to account for algal blooms) (de Hoyos et al. 2014). Spain uses MASRP (i.e., with the metric percentage of cyanobacteria). NMASRP addresses eutrophication pressure in Mediterranean reservoirs. This report does not discuss the development of new or revised ecological assessment method for phytoplankton according to finalized IC results, but the application of the existing NMASRP phytoplankton assessment method as intercalibrated in the Med GIG (including existing MEP values and EQRs), into the national dataset. NMASRP values are calculated as annual mean. This dataset contains data collected during the 2012-2015 sampling campaign, and in particular 53 NMASRP values for LM 5/7 and 18 NMASRP values for LM 8 reservoirs arising from 139 and 56 samplings, respectively.